Analysis of the Impact of Trademark Rights Violations on the Indonesian Economy - Delviani Damanik; Dewi Kentri Saragih; Sabina Saeca Gultom; Arman Febrian; Abdurahman Nafis; Mhd Ridwan Hutabarat (ISNU Nine-Star Multidisciplinary Journal, 2025)
This study aims to analyze the impact of trademark infringement on the Indonesian economy, using a normative juridical approach through legislative and conceptual approaches. The data sources used are secondary data, including primary legal materials, such as Law Number 20 of 2016 concerning Trademarks and Geographical Indications, as well as secondary legal materials, such as journals, books, and related research reports. Data collection techniques are carried out through literature studies and legal document analysis. The results of the study indicate that trademark infringement can harm the Indonesian economy in the form of lost tax revenue, decreased competitiveness of domestic products, and losses for businesses and consumers. The discussion identifies challenges in law enforcement and the need for regulatory updates and strengthened cooperation between related parties to minimize the impact of violations. This study concludes that stricter legal protection for trademark rights and public education on the importance of choosing legitimate products can improve Indonesia's economic climate, create a fairer market, and increase state revenues from the tax sector and international trade.